2020
DOI: 10.1136/bmjdrc-2019-000945
|View full text |Cite
|
Sign up to set email alerts
|

Heredity of type 2 diabetes confers increased susceptibility to oxidative stress and inflammation

Abstract: Introduction and objectiveHeredity of type 2 diabetes mellitus (T2DM) is associated with greater risk for developing T2DM. Thus, individuals who have a first-degree relative with T2DM (FDRT) provide a natural model to study factors of susceptibility towards development of T2DM, which are poorly understood. Emerging key players in T2DM pathophysiology such as adverse oxidative stress and inflammatory responses could be among possible mechanisms that predispose FDRTs to develop T2DM. Here, we aimed to examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Genetic variants of oxidant-antioxidant status have been shown to increase the risk of several malignancies including, breast cancer, gliomas, and gastric cancer [ 41 , 42 ] [ 43 ]. It has been also shown that the first-degree relatives of patients with diabetes mellitus have higher levels of oxidative stress than the controls [ 44 ] [ 45 ] [ 46 ]. In this study, we found higher serum levels of lipid peroxidation, as measured by MDA in the first-degree relatives of GC patients compared with controls, even after adjustment for age, sex, and smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants of oxidant-antioxidant status have been shown to increase the risk of several malignancies including, breast cancer, gliomas, and gastric cancer [ 41 , 42 ] [ 43 ]. It has been also shown that the first-degree relatives of patients with diabetes mellitus have higher levels of oxidative stress than the controls [ 44 ] [ 45 ] [ 46 ]. In this study, we found higher serum levels of lipid peroxidation, as measured by MDA in the first-degree relatives of GC patients compared with controls, even after adjustment for age, sex, and smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has also been implicated in the development of complications of diabetes such as nephropathy and neuropathy [32,33]. A recent study found that individuals with heredity of type 2 diabetes have an increased susceptibility to oxidative stress and inflammation following a high-carbohydrate meal [34].…”
Section: Discussionmentioning
confidence: 99%
“…Both oxidative stress and inflammation interfere with insulin signaling ( Wen and Duffy, 2017 ), leading to insulin resistance, DM, and related complications ( Baig et al, 2020 ), and these processes are considered to be important components of the pathogenesis of DM. Persistent oxidative stress and the destruction of normal cellular redox homeostasis typically occur alongside chronic inflammation and the two are highly interrelated; therefore, we will discuss their impact on ECs in diabetes together ( Mallard et al, 2020 ).…”
Section: Mechanism Of Diabetic Damage To Endotheliamentioning
confidence: 99%